Investigation of Polycarbazoles Thin Films Prepared by Electrochemical Oxidation of Synthesized Carbazole Derivatives - Contal, Emmanuel; Sougueh, Charmaké Moussa; Lakard, Sophie; Et Taouil, Abdeslam; Magnenet, Claire; Lakard, Boris (Frontiers in Materials, 2019)
Polycarbazole and its derivatives have advantages of good environmental stability, electrochromic properties and photoconductivity which have attracted considerable attention because of their potential industrial applications in electroluminescent applications, rechargeable batteries, and light emitting diodes. They have the possibility of different position substitution (carbon C3-C3' or N) that lead to different electropolymerization behaviors. However, the N position facilitates the grafting of various derivatives of interest and permits not to modify so much the radical cation formation during electropolymerization. In this paper, carbazole and its derivatives were electrochemically oxidized in acetonitrile solutions leading to the formation of thin polymer films. The morphological features and electrochemical properties of the as-formed polymer films were investigated in detail. Thanks to these experiments, the influence of the substitution on the properties of the polymer films was evidenced and discussed. In addition, fast electrochemistry experiments were carried out on platinum microelectrodes within 50–1,000 V/s scan speed range. Reactivity of carbazole derivatives radical cations and dimers was investigated through these experiments. Thermodynamic and kinetic information (e.g., redox standard potential, heterogeneous, and dimerization rate constants) was extracted after coupling with electrochemical simulations.